EFL students' perspectives on the use of Wordwall.net as vocabulary learning media (ELT Forum: Journal of English Language Teaching, 2022)
Using ICT tools to teach vocabulary is a commonly researched topic in language teaching. Many popular web tools, such as Kahoot and Quizizz, are used as experimental tools with learners to investigate how effectively they enhance learners' vocabulary. This study analyzed the students' perceptions of Wordwall.net, a less known and researched game-based web tool, in their vocabulary learning. This study was conducted since there is still limited research conducted in Indonesia that analyses the students' perception of using Wordwall.net in English vocabulary learning. This research design was survey research with a sample of 29 8th-grade students at one of the Junior High Schools in Bengkulu Tengah. The data were collected using a close-ended questionnaire. It was analyzed quantitatively by implementing the Likert scale. The result of this research found that most students' perception of the use of Wodwall.net in their vocabulary learning was positive. Their feeling about Wordwall.net was great. They enjoyed the teamwork and competition; they perceived Wordwall.net as an exciting, interesting, motivating & fun web tool to learn vocabulary. From the students' perceived effects of using Wordwall.net, Wordwall.net was a kind of awaited learning media for the students. In addition, Wordwall.net also influenced the students' engagement with the web tool and the classroom. It indicated that the students paid more attention to the learning process. The researchers strongly recommended that teachers start using Wordwall.net to learn vocabulary based on the results.